Entrepreneurship Intention Of University Students In Ho Chi Minh City, Vietnam - Viet Anh, Nguyen Ho; Nguyen, Vu Nguyen Khanh; Hiep, Nguyen Pham Ngoc; Khanh, Duong Duy; Duc, Nguyen Thanh; Sang, Phan Trung (Technium Social Sciences Journal, 2021)
This study aims to exam a model of the factors affecting the students’ entrepreneurial intention at the universities located in Ho Chi Minh City, Vietnam. The data was collected from 255 universities students from various faculties. The study examines the theoretical model comprising of 07 factors as (1) Personal knowledge and experience, (2) Influence of family and friends, (3) Personal Attitudes, (4) Personality, (5) Perceived behavioral control, (6) Educational programs and (7) Capital. The results show that all 7 factors are impacting on entrepreneurial intention of students. Since then, the results are also providing useful recommendations to improve the success of entrepreneurship activities among students at the University.